An Approach from the Plithogenic DEA to the Calculation of the Efficiency of a Pedagogical Strategy on Basic Digital Competencies in Students of the Basic Education Program at the Bolivarian University of Ecuador - Johanna Irene Escobar Jara (Neutrosophic Sets and Systems)
In the context of higher education, the evolution towards a full integration of digital technologies has been significant globally, but its effective implementation varies between different regions and institutions. In Latin America, the adoption of information and communication technologies (ICTs) has been uneven, despite efforts to incorporate digital tools into education. Significant gaps in infrastructure and teacher training persist, which limit educational quality and the full development of digital skills in students. This paper aims to measure the impact of implementing a pedagogical strategy on developing basic digital skills and how it improves the pedagogical skills and innovation capacity of students in the Basic Education career at the Bolivarian University of Ecuador. To achieve this goal, a group of students who receive a program benefiting from this strategy are evaluated. Plithogenic Data Envelopment Analysis (DEA) is used for data representation and processing. On the one hand, plithogeny is used to deal with data of different natures; it is a multivariate theory. DEA is a theory based on linear programming that measures the efficiency between input and output variables for multi-criteria decision problems. The combination of both tools allows the research objective to be met.